NORTH CAROLINA NURSES WITH SUBSTANCE USE DISORDER: A BIOPSYCHOSOCIAL EXPLORATION - Griffith, Sara A (East Carolina University, 2021)
Substance abuse has impacted society economically through increased healthcare costs and lost work productivity; however, the greatest impact is the loss of life. Healthcare professionals such as nurses, physicians, pharmacists, and dentists are at risk to the detrimental impact of substance use disorder (SUD) on their professional and personal lives. Approximately 10-15% of the nursing workforce have a SUD, which is consistent with the rate the general population. There are programs offered by state boards of nursing to assist nurses in returning to nursing practice in a safe, monitored, and structured process in order to meet the regulatory mandate of public protection.The purpose of this study was to examine the characteristics of nurses who enrolled in the North Carolina Board of Nursing's Alternative Program (AP) for SUD and the explore the differences between the characteristics of nurses who complete the AP and those who do not complete the AP. Relationships among biopsychosocial domains were examined utilizing the Biopsychosocial Theoretical Framework. A retrospective descriptive correlational study was conducted of a sample of 285 nurses who were enrolled in the NCBON's AP from January 1, 2011 to December 31, 2014. Nurses were reported to the NCBON due to concerns related to impairment while on duty, discrepancies identified in an agency-controlled substance audit, and pharmacy reports such as waste and high user reports. The NCBON's AP monitors nurses for a period of 3-5 years. The data collection for this data set concluded in 2018 after each nurse in the cohort either completed the AP or did not complete the AP. The participants in this study were primarily female and were licensed as a registered nurse. The mean age for the study sample was 39 and the participants were licensed as a nurse for about 10 years at the time of enrollment in the AP. Opioids were the primary substance abused. The exploration of the relationships among the biopsychosocial variables identified returning to nursing practice (work) as a key characteristic of a nurse completing the NCBON's AP. Other characteristics that were correlated with completion of the AP were prior treatment for SUD, phentermine use, and obtaining legitimately prescribed controlled substances. A logistic regression analysis was performed that identified a unique statistically significant contribution of phentermine use and return to work. A concurrent mental health diagnosis and chronic pain were not statistically significant in relation to completing the AP. These findings support that there are various factors that influence the development and diagnosis of a SUD. While these characteristics are important to identify, it is also important to recognize that recovery is a life-long and difficult process. This study provides a foundation of evidence related to the characteristics of nurses who participated in the NCBON's AP during a specific timeframe and an exploration of the biopsychosocial factors that lead to completion of the NCBON's AP.
Keywords: nursing regulation; alternative to discipline program; Substance-Related Disorders; North Carolina